2011
DOI: 10.1016/j.prevetmed.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Horse owners’ biosecurity practices following the first equine influenza outbreak in Australia

Abstract: A cross-sectional study was conducted involving 759 Australian horse owners to determine their biosecurity practices and perceptions one year after the 2007 equine influenza outbreak and to investigate the factors influencing these perceptions and practices. A web link to an online questionnaire was sent to 1224 horse owners as a follow-up to a previous study to obtain information about biosecurity perceptions and practices, impacts of the 2007 EI outbreak, demographic information and information about horse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 18 publications
1
35
2
2
Order By: Relevance
“…This suggestion is consistent with cognitive behaviour theories such as the Protection Motivation Theory, which outlines that a person's perceptions of a behaviour's practicality and effectiveness are linked to their motivation and compliance with the behaviour. 21,22 Consistently, a previous study linked horse owner's perceptions of biosecurity effectiveness to compliance with recommended measures following the 2007 equine influenza outbreak 19 and in the current study we found that those reporting hand-washing/ glove wearing to be ineffective and biosecurity to be not practical, also considered it somewhat likely that they themselves spread infectious disease from one client's horse to another. It is evident that greater emphasis needs to be placed on the practical aspects of implementing biosecurity measures and how to overcome deterrents in future biosecurity training for students and practicing equine veterinarians.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This suggestion is consistent with cognitive behaviour theories such as the Protection Motivation Theory, which outlines that a person's perceptions of a behaviour's practicality and effectiveness are linked to their motivation and compliance with the behaviour. 21,22 Consistently, a previous study linked horse owner's perceptions of biosecurity effectiveness to compliance with recommended measures following the 2007 equine influenza outbreak 19 and in the current study we found that those reporting hand-washing/ glove wearing to be ineffective and biosecurity to be not practical, also considered it somewhat likely that they themselves spread infectious disease from one client's horse to another. It is evident that greater emphasis needs to be placed on the practical aspects of implementing biosecurity measures and how to overcome deterrents in future biosecurity training for students and practicing equine veterinarians.…”
Section: Discussionsupporting
confidence: 82%
“…The findings of this study are supported by a previous study with Australian veterinarians, which also suggested the need for more practical biosecurity training as it found little uptake of appropriate personal protective equipment use in practice. 11 Younger veterinarians may have lower levels of biosecurity compliance similar to younger horse owners 19 . Implementing biosecurity measures might be perceived as a greater inconvenience by younger veterinarians due to the associated costs in terms of time and effort, making it less practical for them to perform than for older veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…Past research on attitudes and perceptions specific to the biosecurity domain has predominantly been conducted in the animal industry, examining issues such as foot and mouth disease, equine influenza and other diseases found in commercial animal production (Buetre et al 2013;Hoe and Ruegg 2006;Schemann et al 2011). Results have typically demonstrated that farmers perceive the level of investment required to implement biosecurity practices on-farm as costly, in terms of both financial cost and effort.…”
Section: The Psychology Of Biosecuritymentioning
confidence: 99%
“…While much of the empirical psychology literature on behavioural adherence comes from the health and sport/exercise psychology domains, adherence is a key concept in the study of biosecurity engagement. Schemann et al (2011) examined the concept of adherence in an evaluation of biosecurity compliance amongst horse owners 1 year after the 2007 EI outbreak, when biosecurity compliance was presumably at its peak. Results showed that 50 % reported high biosecurity compliance 1 year post-EI, and 30 % reported low compliance.…”
Section: Socio-contextual Factorsmentioning
confidence: 99%
“…Biologically important two‐way interactions of the explanatory variables in the final model were examined and retained if significant ( P < .05).75 …”
Section: (B) Describe the Rationale For Examining Subgroups And Intmentioning
confidence: 99%